2023
DOI: 10.1029/2023ja031652
|View full text |Cite
|
Sign up to set email alerts
|

Climatology, Long‐Term Trend and Solar Response of Na Density Based on 28 Years (1990–2017) of Midlatitude Mesopause Na Lidar Observation

Chiao‐Yao She,
David A. Krueger,
Zhao‐Ai Yan
et al.

Abstract: The climatology of earth's Na density over Fort Collins, CO (41°N, 105°W) based on nocturnal Na lidar observations between 1990 and 1999 was reported by She et al. (2000, https://doi.org/10.1029/2000gl003825). Based on a continued 28‐year data set between 1990 and 2017 with the latter part observed over Logan, UT (42N, 112W), we update the seasonal variations between 80 and 110 km. This data set is also used to deduce long‐term responses of Na density (profile) between 75 and 110 km, showing a positive linear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Second, except for the period of May to August, the centroid altitude of calcium atoms at Yanqing is slightly higher (less than 1 km) than that observed in Kühlungsborn. It is noteworthy that She et al, 2023, reported a declining trend in the centroid altitude of sodium atoms from 1990 to 2017, correlating with solar flux [30]. To further explore this, we calculated the monthly average sunspot number, obtaining a mean of 56.69/month for December 1996 to December 1998 and 34.13/month for March 2020 to July 2022.…”
Section: Comparison With Observations At Kühlungsborn (54 • N)mentioning
confidence: 98%
See 1 more Smart Citation
“…Second, except for the period of May to August, the centroid altitude of calcium atoms at Yanqing is slightly higher (less than 1 km) than that observed in Kühlungsborn. It is noteworthy that She et al, 2023, reported a declining trend in the centroid altitude of sodium atoms from 1990 to 2017, correlating with solar flux [30]. To further explore this, we calculated the monthly average sunspot number, obtaining a mean of 56.69/month for December 1996 to December 1998 and 34.13/month for March 2020 to July 2022.…”
Section: Comparison With Observations At Kühlungsborn (54 • N)mentioning
confidence: 98%
“…Table 1 presents the parameters of the Ca and Ca + lidar system. 30 mJ for Ca and Ca + ions, respectively), a narrow bandwidth (169.3 MHz and 154.6 MHz for Ca and Ca + ions, respectively), robust system stability, and the ability to generate a uniform and adjustable laser spot. The OPO lidar utilizes an all-solid-state technology, with the laser component providing control over the output spot.…”
Section: The Opo Ca-ca + Lidarmentioning
confidence: 99%